British and U.S. post-neutrality policy in the North Atlantic area 09.04.1940-1945: The role of Danish representatives. - Hanna i Horni (2010)
Following the German occupation of Denmark on April 9th 1940 Danish representatives were left to their own devices and their positions in their respective host-countries became very much dependent upon the goodwill shown to them by their host-governments and, in the case of the Faroe Islands, Iceland and Greenland, the governments and officials of the occupying forces. With their connections with the Government in Copenhagen severed the main task of the Danish representatives was to secure Danish interests in the North Atlantic Territories as well as elsewhere. The fact that Denmark had not put up a fight to defend her neutrality and the subsequent collaboration of the Danish Government with the German occupiers counted against the Danish representatives abroad. However, the Danes were able to exercise a remarkable level of influence on the British and Americans with regard to their policies towards the North Atlantic Area. The extent of influence was mainly due to the entrepreneurship of each individual, the constitutional status of the territory as part of the Kingdom of Denmark, and also due to strategic importance attached by the occupying forces' governments to the occupied territories in question. This latter point became especially apparent in the power struggle amongst the Danish representatives that emerged from the lack of a Danish Government in exile. It became important to the British and the Americans that it was the Danish representative in their country, who emerged as the victor of this power struggle, because that would help to secure their future interests in the North Atlantic territories. The Danish representatives were thus in some cases shown more goodwill and attention than their Norwegian colleagues, although the Norwegians had put up a brave fight against the Germans and had joined the allied side. The North Atlantic area proved very important to the general war policy of the British and Americans during Second World War. British policies were much dependent upon the Americans and Greenland and Iceland became instrumental in the increased involvement of the Americans in the war.